2003
DOI: 10.1038/sj.bmt.1704221
|View full text |Cite
|
Sign up to set email alerts
|

High-dose melphalan followed by radical radiotherapy for the treatment of massive plasmacytoma of the chest wall

Abstract: Summary:We report three cases of massive chest wall plasmacytoma, each greater than 10 cm in diameter, without evidence of overt myeloma, whom we treated with a combination of VAD chemotherapy consolidated by highdose melphalan and autologous peripheral blood stem cell transplantation and radical radiotherapy. All three patients completed all components of their therapy without experiencing any major side effects and one patient has had a durable remission. The other two patients have had disease progression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…SP has been reported to be highly radiosensitive and chemosensitive [5,6,8]. However, as seen in our case and in the other reports [4,9], the prognosis and the sensitivity of SP to radiochemotherapy may be poor, and the course of the disease may be very aggressive.…”
contrasting
confidence: 60%
“…SP has been reported to be highly radiosensitive and chemosensitive [5,6,8]. However, as seen in our case and in the other reports [4,9], the prognosis and the sensitivity of SP to radiochemotherapy may be poor, and the course of the disease may be very aggressive.…”
contrasting
confidence: 60%
“…Therapeutic strategies for solitary plasmacytoma and EMP include surgery, chemotherapy, radiotherapy, along with combined approaches 2 . Although it was showed that solitary plasmacytoma are highly chemoradiosensitive 3,21,22 , many cases of EMP are reported to be insensitive to radiotherapy and chemotherapy 2,19,23 . In eligible patients, radiation therapy in the dose of 40-50 Gy has been suggested providing an excellent locoregional disease control 24 .…”
Section: Fig 5 -A B) the Tumor Forms A Submucosal Duodenal Nodule Wmentioning
confidence: 99%
“…Eight patients (67%) had received radiotherapy before the progenitor cell mobilisation. All patients except one had received previous chemotherapy for a median of four courses (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The most commonly applied regimen was VAD (10 patients).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Other high-risk features observed include nonsecretory PC (6), large PC (7) and persistence of paraprotein after the first line therapy (8). Limited data on ASCT in patients with PC is currently available (9,10). We have therefore evaluated the feasibility and potential efficacy of this approach in patients with high-risk PC who received ASCT in five Finnish transplant centres.…”
mentioning
confidence: 99%